The Improvement of Arabic Language Learning Program in Realizing the World Class University - Mustofa, Syaiful; Febriani, Suci Ramadhanti; Ibrahim, Faisal Mahmoud (Universitas Islam Negeri Raden Intan Lampung, 2021)
Foreign language is one of the fundamental elements in creating the world class university. To realize a world class university, the excellent Arabic language learning program is necessary to meet the needs of international communication in the internal and external environment of the campus. This study aimed to explore and analyze the Arabic language learning program at UIN Maliki Malang. The research data were obtained from the interview with campus governance and direct observation of Arabic learning program activities and the documentation of strategic planning of Arabic language learning programs to create a world class university. The interviews were conducted with 10 people of campus institution governance. The results showed that Arabic language learning program in realizing a world class university is an implementation of the university's vision which is contained in the development of an integrated curriculum and ulul albab character. The curriculum is designed in the form of a